(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
Nitrogen migration depends on fertilizer rates and precipitation and increases in soils with a lighter texture. Based on research conducted on light loamy soil, N-NO3 is rapidly washed out of the 0-15 cm layer and accumulates only slightly in the 15-30 cm layer.